THE ROLE OF GRAFFITI AND MURAL AS ALTERNATIVE PUBLIC SPHERE FOR SOCIETY - Gushendra, Ryan Putra (PEOPLE: International Journal of Social Sciences, 2015)
Nowadays, people are deliberately voicing their opinions regarding current issues that happen in Indonesia, which we often see on printed media or even electronic media. However, as the time goes by, people tend to distrust a dominant public sphere, which is media, especially since Presidential Election in 2014. Most media in Indonesia took sides to each parties and it causes a lack of objectivity in order to present news and information. Media conglomeration is also one of the causes of declining people's trust. It encourages street artists to voicing people's aspirations. Graffiti and murals become an alternative public sphere to criticize government's performances and to speak up about their opinions. An ordinary wall which is usually used to be a roadblock is transformed into an interesting and artistic creation to be seen and to be followed more. Graffiti and mural also have important roles for urban society in the middle of unfavorable politics situation lately for citizens and at the same time haven't reached the real civil supremacy and democracy.